A Prospective and Controlled Clinical Trial on Stromal Vascular Fraction Enriched Fat Grafts in Secondary Breast Reconstruction. (28th December 2015) - Tissiani, L. A. L.; Alonso, N.
Abstract : Background. Fat grafting is a tremendous tool in secondary breast reconstruction. Stromal vascular fraction (SVF) enriched fat grafts have been presenting promising results regarding volume maintenance. Methods. We developed a method that produces a superior SVF enrichment rate (2 : 1) in the operating theatre. This prospective and controlled trial analyzed quantitatively and qualitatively fat grafts with (stem cells group, SG) and without (control group, CG) SVF enrichment in secondary breast reconstruction, through MRI-based volumetry, immunophenotyping, and cell counting. Also, patient satisfaction, aesthetic outcomes, and complications were analyzed. Results. Volumetric persistence in the SG was 78, 9% and 51, 4% in the CG; however it did not reach statistical significant difference. CD90 was the only marker highly expressed in the SG and showed a positive correlation with volumetric persistence (r = 0.651, p = 0.03 ). Fat necrosis occurred in 4 patients in the SG and in none in the CG. Patients in the CG showed a trend to be more satisfied. Considering aesthetics, both groups presented improvements. No locoregional recurrences were observed. Conclusions. Results are encouraging despite the fact that SVF enrichment in a higher supplementation rate did not improve, with statistical significance, fat graft volumetric persistence. Enriched fat grafts have proven to be safe in a 3-year follow-up.